MANAJEMEN SERTIFIKASI GURU AL-QUR’AN METODE UMMI DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK (Studi Kasus di TPA Al-Ba’lawi Cikarang) - Suci Dwi Kurniasih; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Penerbit Widina, Widina Media Utama, 2026)
The Ummi Method Quran Teacher Certification is a strategic tool for ensuring the quality of Quran education; however, its implementation in the field has not yet been fully optimized in terms of developing teachers’ pedagogical competencies. This study aims to analyze the management of the Ummi Method Quran Teacher Certification and its contribution to improving teachers’ pedagogical competencies at the Al-Ba’lawi Quran Learning Center in Cikarang. The study employs a qualitative approach with an intrinsic case study design, collecting data through observation, in-depth interviews, and document analysis, which were analyzed using the Miles and Huberman interactive model. The findings indicate that certification management remains largely administrative and focused on technical aspects (tahsin), while post-certification mentoring and evaluation of pedagogical impact have not been optimally implemented. This has hindered the full development of teachers’ pedagogical competencies, particularly in contextual lesson planning, the implementation of active learning strategies, and the conduct of authentic assessment. Therefore, a paradigm shift in certification is needed—moving beyond mere testing toward continuous learning through strengthened mentoring, the development of communities of practice, and the integration of the values of the Ummi Method into the certification management cycle. ABSTRAKSertifikasi Guru Al-Qur’an Metode Ummi merupakan instrumen strategis dalam penjaminan mutu pendidikan Al-Qur’an, namun implementasinya di lapangan belum sepenuhnya optimal dalam mengembangkan kompetensi pedagogik guru. Penelitian ini bertujuan untuk menganalisis manajemen sertifikasi guru Al-Qur’an Metode Ummi serta kontribusinya terhadap peningkatan kompetensi pedagogik guru di TPA Al-Ba’lawi Cikarang. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik, dengan pengumpulan data melalui observasi, wawancara mendalam, dan studi dokumentasi yang dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa manajemen sertifikasi masih cenderung bersifat administratif dan berfokus pada aspek teknis (tahsin), sementara pendampingan pasca-sertifikasi serta evaluasi dampak pedagogik belum berjalan optimal. Hal ini berdampak pada belum berkembangnya kompetensi pedagogik guru secara maksimal, terutama dalam perencanaan pembelajaran kontekstual, penerapan strategi pembelajaran aktif, dan pelaksanaan penilaian autentik. Oleh karena itu, diperlukan transformasi paradigma sertifikasi dari sekadar pengujian menuju pembelajaran berkelanjutan melalui penguatan pendampingan, pengembangan komunitas praktik, serta integrasi nilai-nilai Metode Ummi dalam siklus manajemen sertifikasi.